2011
DOI: 10.1332/204080511x560602
|View full text |Cite
|
Sign up to set email alerts
|

Religious and secular volunteering: a comparison between immigrants and non-immigrants in the Netherlands

Abstract: Using new survey data from the Netherlands, we find that non-immigrants are more likely to volunteer for secular organisations than guest worker immigrants and postcolonial citizen immigrants. In contrast, non-immigrants are less likely to engage in religious volunteering than both immigrant groups. We explain differences in the likelihood of religious and secular volunteering between immigrants and non-immigrants in the Netherlands by differences in level of individual resources, religiosity and having been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 30 publications
3
40
1
Order By: Relevance
“…Suriname is a former colony of the Netherlands and most women from Suriname arrived in the Netherlands around the independence of Suriname or to study (Entzinger 2006). Surinamese women were already more familiar with Dutch culture and the Dutch language before arrival, are predominantly Christian and in general have a better socioeconomic position in the Netherlands (Carabain and Bekkers 2011). Turkish and Moroccan women, on the other hand, did not speak the language at arrival, are predominantly Muslim and are from lower socioeconomic background compared to women of Surinamese origin (Carabain and Bekkers 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suriname is a former colony of the Netherlands and most women from Suriname arrived in the Netherlands around the independence of Suriname or to study (Entzinger 2006). Surinamese women were already more familiar with Dutch culture and the Dutch language before arrival, are predominantly Christian and in general have a better socioeconomic position in the Netherlands (Carabain and Bekkers 2011). Turkish and Moroccan women, on the other hand, did not speak the language at arrival, are predominantly Muslim and are from lower socioeconomic background compared to women of Surinamese origin (Carabain and Bekkers 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Surinamese women were already more familiar with Dutch culture and the Dutch language before arrival, are predominantly Christian and in general have a better socioeconomic position in the Netherlands (Carabain and Bekkers 2011). Turkish and Moroccan women, on the other hand, did not speak the language at arrival, are predominantly Muslim and are from lower socioeconomic background compared to women of Surinamese origin (Carabain and Bekkers 2011). The women differ in their cultural and migration background, yet share their weak position on the Dutch labor market compared to native Dutch and migrant men (Huijnk et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The previous research suggests that participation in volunteering within civil society can act as a 'stepping stone' towards integration for immigrants who seek to establish themselves in their host societies (Handy and Greenspan, 2009). This is because the immigrants who participate in volunteering may improve their human capital and enhance their social networks, which in turn can improve their chances in the formal labor market and aid their civic, social and political integration into the host society (Handy and Greenspan, 2009;Carabain and Bekkers, 2011;Handy and Mook, 2011;Weng and Lee, 2015). However, the previous comparative studies of European countries and single country studies have identified gaps in the propensity to volunteer between immigrants and natives, with natives being more likely to volunteer compared to immigrants (Eimhjellen and Segaard, 2010;Svedberg, von Essen and Jegermalm, 2010;Aleksynska, 2011;Carabain and Bekkers, 2011;Voicu and Şerban, 2012;Fridberg and Qvist, 2014;Qvist, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the immigrants who participate in volunteering may improve their human capital and enhance their social networks, which in turn can improve their chances in the formal labor market and aid their civic, social and political integration into the host society (Handy and Greenspan, 2009;Carabain and Bekkers, 2011;Handy and Mook, 2011;Weng and Lee, 2015). However, the previous comparative studies of European countries and single country studies have identified gaps in the propensity to volunteer between immigrants and natives, with natives being more likely to volunteer compared to immigrants (Eimhjellen and Segaard, 2010;Svedberg, von Essen and Jegermalm, 2010;Aleksynska, 2011;Carabain and Bekkers, 2011;Voicu and Şerban, 2012;Fridberg and Qvist, 2014;Qvist, 2014). An important exception appears to be that immigrants are more likely to participate in religious volunteering compared to natives; at least studies have found this to be the case in the Netherlands and Canada (Carabain and Bekkers, 2011;Wang and Handy, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation